Should National Sharia Board be Restructured to Sustain the Development of Economic Sharia in Indonesia? - Barlinti, Yeni Salma; Dewi, Yetty Komalasari (Indonesian Journal of International Law, 2012)
The economy of Islamic finance has an important role in improving a nation’s economy and has developed rapidly throughout the world including in Southeast Asia. This paper discusses the role of Board of fatwa (and the fatwa itself) within Indonesia governmental structure in order to enhance the economic activities of sharia. The involvement of sharia scholars are needed in the process of regulating economic policies since only few of Indonesian legislators have good understanding in the law of Islamic finance. At the moment, fatwa issued by sharia scholars in economic activities is not legally binding due to its organization structure in Indonesia governmental system. As a result, it creates legal uncertainty not only to business players but more importantly to the society at large on the issue of whether or not the fatwa is mandatory. Therefore restructuring the board of fatwa is a way to provide legal certainty in order to sustain the development of economic sharia in Indonesia as well as in Southeast Asia.